Test of electrical method of determining soil moisture - Schmitz, Nickolas; Elling, Carl G. (My University, 1904)
Introduction: The importance of having a reliable method of determining the amount of soil moisture has been recognized by the formost agriculturalists for a long time. Knowing this many of our exoerimenters have tried to find some accurate method by which they might determine the amount of moisture in the soil. Various methods by different experimenters have been proposed for this purpose but with very little success. In 1885 the New York station buried brick in the ground and taking them up and weighing from day to day. They hoped to be able to determine the amount of moisture, but this proved to be unreliable as well as.inconvenient. Later porous terra cotta was tried but with no better results. Finally a graduated tube was let down in the ground and water allowed to flow through a small opening in the bottom into the soil. it being assumed that the drier the soil the faster the flow, and that the quantity which flows out in a certain time will have some ratio to the amount of water in the soil. While this method was supposed to be accurate, yet it has never been entirely satisfactory.
Citation: Schmitz, Nickolas and Elling, Carl G. Test of electrical method of determining soil moisture. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Soil Moisture; Measurement Techniques; Soil Moisture Measurement Devices; Theses